Pelayanan Pemuridan dalam Gereja Masa Kini - Sari Saptorini; Listari (Matheteuo: Religious Studies, 2021)
The ministry of discipleship in the church has a very important location and role for church growth. To be able to move the congregation to be involved in the ministry of discipleship, it is necessary to make efforts that are more interesting and relevant to the current situation and conditions. Therefore, this article with qualitative research will discuss the ministry of discipleship through video conferences in the church today. The author conducted a literature study on studies that support this theme in order to facilitate the operation of the discipleship service without having to be hampered by the rules of Physical Distancing, namely through video conferences. To assist the analysis process in this study, the authors conducted a data review of various sources of literature in the form of theological journals or books in accordance with the theme, in order to obtain an overview of discipleship services and strategies in dealing with situations and conditions in the service field.